A state‐level analysis of the economic impacts of medical tourism in Malaysia†. (May 2016) - Klijs, Jeroen; Ormond, Meghann; Mainil, Tomas; Peerlings, Jack; Heijman, Wim
Abstract : In Malaysia, a country that ranks among the world's most recognised medical tourism destinations, medical tourism is identified as a potential economic growth engine for both medical and non‐medical sectors. A state‐level analysis of economic impacts is important, given differences between states in economic profiles and numbers, origins, and expenditure of medical tourists. We applied input–output (I–O) analysis, based on state‐specific I–O data and disaggregated foreign patient data. The analysis includes nine of Malaysia's states. In 2007, these states were visited by 341, 288 foreign patients, who generated MYR1, 313.4 m (372.3 m) output, MYR468.6 m (132.8 m) in value added, and over 19, 000 jobs. Impacts related to non‐medical expenditure are more substantial than impacts related to medical expenditure, and indirect impacts are a substantial part of total impacts. We discuss management and policy responses and formulate recommendations for data collection.